2005
DOI: 10.1007/s11745-005-1418-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of palm vitamin E and α‐tocopherol on healing and wound tissue antioxidant enzyme levels in diabetic rats

Abstract: The effect of supplementing 200 mg/kg body weight palm vitamin E (PVE) and 200 mg/kg body weight alpha-tocopherol (alpha-Toc) on the healing of wounds in streptozotocin-induced diabetic rats was evaluated. The antioxidant potencies of these two preparations of vitamin E were also evaluated by determining the antioxidant enzyme activities, namely, glutathione peroxidase (GPx) and superoxide dismutase (SOD), and malondialdehyde (MDA) levels in the healing of dermal wounds. Healing was evaluated by measuring woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
6
37
0
1
Order By: Relevance
“…Glutathione plays a role in antioxidant defense, decreasing in the presence of oxidants and delaying wound healing (26). Studies on patients with diabetes have shown a decrease in erythrocyte GSH levels and increased erythrocyte lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione plays a role in antioxidant defense, decreasing in the presence of oxidants and delaying wound healing (26). Studies on patients with diabetes have shown a decrease in erythrocyte GSH levels and increased erythrocyte lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…New evidences from the studies on diabetic mouse models point to an involvement of oxidative stress in diabetic wound healing and significantly improved wound healing by topical vitamin E. 54,55 Another finding showed vitamin E or α-tocopherol supplementation reduced the levels of lipid peroxides in the wound tissue of diabetic rats, and the wound healing process was enhanced, in particular in the Vitamin E treated animals. 56 Tsoureli-Nikita et al 57 performed a clinical single, blind, placebo controlled study in which 96 atopic dermatitis patients were treated with either placebo or oral vitamin E (400 IE/day) for 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…One study in rats evaluated the role of either vitamin E subfamily by comparing the wound healing properties of ␣ -tocopherol against palm vitamin E extract, which is rich in tocotrienols [26] . Streptozotocin-induced diabetic mice were excision wounded and treated orally with either vitamin E subfamily at 200 mg/kg and compared to controls that were fed olive oil.…”
Section: Vitamin Dmentioning
confidence: 99%